Increasing Neural Stem Cell Division Asymmetry and Quiescence Are Predicted to Contribute to the Age-Related Decline in Neurogenesis - Bast, Lisa; Calzolari, Filippo; Strasser, Michael K.; Hasenauer, Jan; Theis, Fabian J.; Ninkovic, Jovica; Marr, Carsten (Cell Reports, 2018)
Bast and colleagues traced the lineages of single neural stem cells in the brains of young and aged adult mice to shed light on the age-related decline in neurogenesis. Mathematical modeling of lineage dynamics revealed changes in the behavior of neural stem cells with age.
CRIS-Team Scopus Importer:2023-03-08
Keywords: adult neurogenesis; computational model; lineage tracing; lineage tree simulation; model averaging; moment equations